2015
DOI: 10.1007/s00253-015-6537-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient removal and biogas upgrading by integrating freshwater algae cultivation with piggery anaerobic digestate liquid treatment

Abstract: An integrated approach that combined freshwater microalgae Scenedesmus obliquus (FACHB-31) cultivation with piggery anaerobic digestate liquid treatment was investigated in this study. The characteristics of algal growth, biogas production, and nutrient removal were examined using photobioreactor bags (PBRbs) to cultivate S. obliquus (FACHB-31) in digestate with various digestate dilutions (the concentration levels of 3200, 2200, 1600, 1200, 800, and 400 mg L(-1) chemical oxygen demand (COD)) during 7-day peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(49 citation statements)
references
References 27 publications
2
44
1
2
Order By: Relevance
“…Concomitantly, CO 2 and other undesirable compounds present in the biogas, such as the toxic and corrosive H 2 S, could be removed (Bahr et al, 2014), ultimately adding value to filtered biomethane. Xu et al (2015) demonstrated the effects of desulphurized biogas on increased nutrient removal by axenic culture of microalgae Scenedesmus obliquus. Nonetheless, considering that H 2 S present in the biogas (up to 5000 ppm; Kao et al, 2012a) could exert some inhibitory effects on microalgae, further studies using raw biogas is warrant to anticipate field scale performance.…”
Section: Microalgamentioning
confidence: 99%
“…Concomitantly, CO 2 and other undesirable compounds present in the biogas, such as the toxic and corrosive H 2 S, could be removed (Bahr et al, 2014), ultimately adding value to filtered biomethane. Xu et al (2015) demonstrated the effects of desulphurized biogas on increased nutrient removal by axenic culture of microalgae Scenedesmus obliquus. Nonetheless, considering that H 2 S present in the biogas (up to 5000 ppm; Kao et al, 2012a) could exert some inhibitory effects on microalgae, further studies using raw biogas is warrant to anticipate field scale performance.…”
Section: Microalgamentioning
confidence: 99%
“…employed swine waste‐water‐derived biogas to growth native microalgal strains and found that CO 2 was completely removed from raw biogas at 219.4 ± 4.8 mg L −1 d −1 , with a biomass yield of 1.1 ± 0.2 g L −1 and growth rate of 141.8 ± 3.5 mg L −1 d −1 . Similar studies also demonstrated that microalgal‐based waste‐water treatment processes could benefit from in situ CO 2 ‐rich biogas . However, the photosynthetic production of oxygen could potentially lead to the explosion of the gas mixture and would therefore necessitate oxygen separation .…”
Section: Waste Streams For Microalgal Cultivationmentioning
confidence: 99%
“…Similar to the conventional activated sludge process, algal systems have traditionally been employed for wastewater treatment, relying on their ability to assimilate nutrients such as nitrogen and phosphorus from the wastewater and use them for their growth. [1][2][3][4] A previous study showed that a combination of algae with activated sewage obtained good nutrient removal rates and promoted algal growth. 5 This suggests that microbes from activated sewage promote nutrient removal and benefit algal growth.…”
Section: Introductionmentioning
confidence: 99%